Front Matter (Journal of the Assembly for Expanded Perspectives on Learning, 2006)
Editors' Message Leaping into Uncertainty: Teaching and Learning beyond Logic and Reason In 1846, Soren Kierkegaard set forth the limits of logical systems and objective truth, neither of which can shed light on the important questions of life. “In logical systems,” the nineteenth century Danish philosophy argues, “nothing may be incorporated that has a relationship to existence, that is not indifferent to existence” (141) because a logical system is purely speculative. Existence is an actuality, a doing. Logical systems cannot account for the necessary leap in life between almost doing something—thinking about doing something (and Kierkegaard’s example is taking the bar exam)—and actually doing the thing. Similarly, objective knowledge “goes along leisurely on the long road of approximation,” but never hurries to grapple with the material enactment of its contemplation. Unlike Socrates, Kierkegaard says, who posits the “if” of immortality and then, by drinking hemlock, leaps into the uncertainty of that “if” to plummet its possibilities, logical systems and objective truth never confront the if. However, subjective truth can inform questions of existence because, spurred by passion, it “contend[s] with uncertainty” and focuses not on the object of inquiry but on the relationship between the inquirer and the object of inquiry. It focuses on the space between, on the necessary leap between. Here is where we can find answers that will shed light on the important questions of our existence. The essays in this volume align with Kierkegaard and embrace the possibilities of “if”; they emphasize in various ways the vitality and vitalness of leaping into uncertainty for it is here that marvelous learning potential and teaching moments exist. We open with Lynn Z. Bloom and Carla Hill, who, in “High Stakes Gambling in the Master Class,” chart the risk and rewards of “if.” From the perspectives of a honors thesis advisor and an advisee, the authors examine what they call the “unarticulated intangibles” that enable a student to produce quality work, seemingly out of “thin air.” At the heart of this process is a high stakes gamble where teacher and learner both “play their hunches” and thus plunge into uncertainty. By trusting to a belief beyond logic and reason, they both “hit the jackpot.” Bloom and Hill provide a template for leaping into uncertainty and demonstrate its importance—the leap and the uncertainty—for teaching and learning. Our remaining authors also explore the rewards (and the fears) of diving into the possibilities of if, and they do so from perspectives that privilege, in turn, the uncertainties of bodies, emotions, and creativity, all realms that align with and exist beyond logical systems and objective truth. Judith Beth Cohen and Carolina Mancuso, in separate articles, focus on the role of what Cohen calls the “missing body’ in education. In “The Missing Body: Yoga and Higher Education,” Cohen claims that student passivity is one of the greatest obstacles to learning; such passivity results in part from teaching strategies that treat students as “talking heads” rather than learning bodies. Cohen proposes that Yoga can combat student passivity through “kinesthetic, somatic, and cognitive integration.” Also concerned with the Western division between mind and body, Carolina Mancuso in “Bodies in the Classroom: Integrating Physical Literacy,” argues for the importance of leaping into the body to learn with it instead of in spite of or against it. She says, “It is as if a shroud covers the depth and breadth of the body’s capability, and we fear its power over us.” Mancuso advocates helping students access and explore their “body stories” as an essential move in tapping the richness of uncertain knowledge that can lead to Kierkegaard’s subjective truth. Hildy Miller and Stephanie Paterson shift attention from the body as a whole organism to one aspect of bodies: the domain of emotions. Both zero in on the importance of emotion in teaching and learning, the former arguing for a rhetoric of desire and the latter exploring the lash of fear. In “Writing Aphrodite: Imagining a Rhetoric of Desire for a Feminist Writing Course,” Miller identifies a nagging problem with students’ academic writing: “a lack of feeling and aesthetic qualities, a general joylessness in its language, and a repetitiveness in its worn out discourse forms.” Such writerly ennui especially affects women who continue to feel displaced in the academic milieu. Her response is a rhetoric of desire which can reanimate student, especially women’s, writing. The vehicle of that reanimation is the archetypal image of Aphrodite, who, because she stands for “the most audacious creativity,” can serve as an “image for a feminist rhetoric of desire.” In “‘Lashing Out at “Intellectuals”’: Facing Fear on Both Sides of the Desk,” Paterson adds another dimension to emotions. She explores the way in which fear of intellectual confusion—engendered by the “opacity” of academic prose—can motivate a student to attack through writing a teacher’s agenda. Reciprocally, Paterson explores her own fear—a panicked reaction to what was initially perceived as a personal attack—that guided her response. In a student-teacher dialogue, both explore the terrors of learning and teaching so that they might discover not how to avoid fear and uncertainty but how to learn from and in the midst of both. Finally, Rich Murphy and Susan Schiller return us to questions of curriculum. How might the leap into uncertainty be codified through a curriculum or a course syllabus? Murphy in “McLuhan’s Warning, Frye’s Strategy, Emerson’s Dream” offers a curricular vision based on writing poetry. He argues for the place of poetic writing in all English classes, from literature to WAC programs. Such writing, Murphy contends, requires students to engage in associative and inductive thinking, leading to realization of the “dream of the citizen-poet,” an individual who can shape a creative life that contributes to the civic good of the community. Susan Schiller in “Uniting Creativity and Research: A Holistic Approach to Learning” advocates a sea change in the traditional approach to the research paper. Creativity—grappling with chaos and uncertainty—has been stripped from conventional research writing pedagogy. The goal is not to separate research and creativity but to balanced them. One way to do this is through a holistic pedagogy that engages the learner’s intellect, body, spirit, and social being in the research enterprise. She demonstrates the possibilities of such an approach with examples of her students’ work in two courses based on holistic pedagogy. That which is certain, the OED tells us, is “determined, fixed, settled; not variable or fluctuating; unfailing.” So a certainty is a truth that is likewise, determined, fixed, and settled. It is a truth that is done, bereft of possibilities. An uncertainty, however, is ripe with potential, ripe with learning, ripe with insights into the issues that continue to beg for our attention. The essays in this volume of JAEPL invite us to leap into that uncertainty and find there moments of learning and teaching. Works Cited Kierkegaard, Soren. “Possible and Actual Theses by Lessing.” Contemporary Philosophy. Ed. Walter Kaufmann and Forrest E. Baird. Englewood Cliffs, NJ: Prentice Hall, 1994. 140–49.